Strengthening the Implementation of Capacity Activities on the Development of Village Government Apparatus Resources in Gorontalo Regency - Junus, Dikson; Napir, Suaib; Nuna, Muten; Harun, Nur Istiyan; Marzaman, Aitika Puspita (Journal of Indonesian Scholars for Social Research, 2022)
The research method used qualitative data analysis, including data collection; data condensation/data simplification; presentation of data, and conclusions/verification. Data were obtained through interviews, observation, and documentation. The study results show that there is still a problem that becomes an obstacle for village government officials in Gorontalo Regency in maximizing their role in development planning, so efforts are needed to improve further the development planning capabilities of the village government apparatus. A level of quality planning and good development management is necessary for government officials. They know the strengthening of the implementation of capacity activities in the development of village government apparatus resources in Gorontalo district. Based on this, a series of activities are needed to encourage the improvement of village government apparatus in a Village Development Planning Workshop and assistance in carrying out village development planning.